Allocating Scarce Medical Resources: Using Social Usefulness as a Criterion. Issue 4 (19th May 2019) - Selvaraj, D.; McClelland, A.; Furnham, A.
Abstract : This study aimed to determine if people would use social usefulness as a criterion when allocating a kidney to potential recipients. Participants ( N  = 281) ranked hypothetical patients in order of priority to receive the kidney, using only information on the patients' volunteering record, intelligence, emotional intelligence, and attractiveness. The results showed that volunteers were prioritized over nonvolunteers, highly intelligent patients over those with average intelligence, patients with high emotional intelligence over those with average emotional intelligence, and good-looking patients over average-looking patients. There was little evidence of personal favoritism. Implications and limitations are discussed.